Ikigai the Japanese secret to a long and happy life - Garcia, Hector (London Hutchinson, 2022)
According to the Japanese, everyone has an ikigai?a reason for living. And according to the residents of the Japanese village with the world?s longest-living people, finding it is the key to a happier and longer life. Having a strong sense of ikigai?where what you love, what you?re good at, what you can get paid for, and what the world needs all overlap?means that each day is infused with meaning. It?s the reason we get up in the morning. It?s also the reason many Japanese never really retire (in fact there?s no word in Japanese that means retire in the sense it does in English): They remain active and work at what they enjoy, because they?ve found a real purpose in life?the happiness of always being busy.
Keywords: Ikigai